(untitled) (Revista do Tribunal Regional Federal da 3ª Região, 2018)
This paper seeks to provide a brief explanation on the issue of the justiciability of rights related to state activity within the realization of social rights and failures of everyday procedural practice in respect to the broad, real and effective contradictory. Obviously, there is no claim to exhaust the subject in its various possibilities, or investigate all the issues in a similar way. What is sought is to score some specific issues related to judicial cognition in complex materials whose natural environment is the executive branch. From the analysis of a specific procedural point of cases involving public policy, we pointed out a case where the absence of contradictory and irregular formation of the procedural relationship leads to misleading results when considered in a broader spectrum cognition.